VISUAL NARRATIVE: READING MEDIATION IN EARLY CHILDHOOD EDUCATION - Lorenzet, Fabiana Lazzari; Ramos, Flavia Brocchetto; Souza, Renata Junqueira de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2021)
With the goal of contributing to the literacy processes of 4-year-old children, this article investigates peculiarities about how children of that age read the visual narrative of Ladrao de galinha by Beatrice Rodriguez. The research has a qualitative and exploratory approach and part of the selection and analysis of an integral part of the Program's Early Childhood Collection National Library of the School (PNBE) 2014, followed by construction and application of a proposal for mediation of reading with children in groups, in order to analyze how they act in the process of construction of sense of visual narratives, from intentionally planned situations of mediation. As a result of the study, we point out contributions from the literary reading of the picture book in the daily school life of pre-school children. We also verify that children, in situations of interaction, help, complement, converge, diverge, express their opinions through speech or other forms of expression. In summary, the book of images proved to be a valuable cultural object that promotes interaction and autonomy.
Keywords: Mediation; Literary reading; Early childhood education